2003
DOI: 10.1104/pp.103.022129
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Induced Gene Expression and Protein Localization of a Cell Wall-Associated Receptor Kinase in Arabidopsis

Abstract: Here, we report the aluminum (Al)-induced organ-specific expression of a WAK1 (cell wall-associated receptor kinase 1) gene and cell type-specific localization of WAK proteins in Arabidopsis. WAK1-specific reverse transcriptase-polymerase chain reaction analysis revealed an Al-induced WAK1 gene expression in roots. Short-and long-term analysis of gene expression in root fractions showed a typical "on" and "off" pattern with a first peak at 3 h of Al exposure followed by a sharp decline at 6 h and a complete di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(160 citation statements)
references
References 89 publications
3
155
0
2
Order By: Relevance
“…Indeed, expression of WAK1 in Arabidopsis was found to be induced by aluminum treatment (Sivaguru et al, 2003), and WAKL4 is related to mineral nutrition responses (Hou et al, 2005). Wall-associated kinases are necessary for normal cell enlargement (Cosgrove, 2001;Wagner and Kohorn, 2001), and in barley and rice, WAK genes were found to affect root growth Gupta, 2008, 2011;Kaur et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, expression of WAK1 in Arabidopsis was found to be induced by aluminum treatment (Sivaguru et al, 2003), and WAKL4 is related to mineral nutrition responses (Hou et al, 2005). Wall-associated kinases are necessary for normal cell enlargement (Cosgrove, 2001;Wagner and Kohorn, 2001), and in barley and rice, WAK genes were found to affect root growth Gupta, 2008, 2011;Kaur et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An inducible reduction in WAK protein accumulation has been shown to reduce plant cell expansion and result in stunting of roots and shoots (Lally et al 2001;Wagner and Kohorn 2001). On the other hand, ectopic overexpression of WAK1 has been shown to increase tolerance of roots to toxic aluminum concentrations (Sivaguru et al 2003). Also, root elongation in loss-of-function mutations of either WAKL4 or WAKL14 is reported to be more or less tolerant to certain metal ion stresses ( Jackson et al 2004).…”
Section: /Rfo1mentioning
confidence: 99%
“…Arabidopsis demonstrated that they are involved in various functions of plants, including pathogen resistance (He et al 1998), heavy metal tolerance (Sivaguru et al 2003) cell elongation and plant development (Lally et al 2001;Wagner and Kohorn 2001).…”
Section: Functional Studies Of Different Wak Members Inmentioning
confidence: 99%
“…WAKs are encoded by five tightly linked and highly similar genes (WAK1-WAK5) in Arabidopsis thaliana, and are expressed in leaves, meristems and cells undergoing expansion (He et al 1996(He et al , 1999Wagner and Kohorn 2001). WAK gene expression is also induced by pathogens, wounding, Aluminum toxicity and numerous other stresses (He et al 1996;Wagner and Kohorn 2001;Sivaguru et al 2003).…”
Section: Introductionmentioning
confidence: 99%